Performance Evaluation of In Vitro Screening and Diagnostic Kits for Hepatitis C Virus Infection - Murayama, Asako; Momose, Haruka; Yamada, Norie; Matsubayashi, Keiji; Muramatsu, Masamichi; Hamaguchi, Isao; Kato, Takanobu (Frontiers in Cellular and Infection Microbiology, 2022)
Aim A reliable kit with high sensitivity and specificity is indispensable for diagnosing hepatitis C virus (HCV) infection. Detection kits for anti-HCV antibodies (anti-HCV) are used for screening, and quantification kits for HCV RNA and HCV antigen (Ag) are used for the definite diagnosis of HCV infection or the evaluation of the pathological condition of and therapeutic effects in patients with chronic hepatitis C. Several kits are currently available for these purposes and are provided for clinical use in Japan. In this study, we aimed to evaluate the performance of these kits. Methods We used International Standards for HCV RNA and HCV Ag and a regional reference panel to evaluate the performance of thirteen anti-HCV, five HCV RNA, and two HCV Ag kits. Results All specimens in the regional reference panel were diagnosed correctly by all anti-HCV kits, although the distributions of the quantified values varied, and the ratios of titer classification were not identical across kits. All HCV RNA kits quantified the International Standard with minimum deviation and diagnosed the specimens of the reference panel correctly. The quantified values of the International Standard by two HCV Ag kits were inconsistent. HCV Ag titers of some specimens were underestimated owing to the amino acid polymorphisms in comparison with HCV RNA titers. Conclusions The evaluation with International Standards and the regional reference panel was useful for assessing the quality of screening and diagnostic kits for HCV infection, and such quality control is essential for the clinical usage of these kits.